The The Comparison of Lexical Bundles in EFL Teachers’ Talk between Non-native and Native English Teachers - Lorenna, May; Fitriati, Sri Wuli; Widhiyanto, Widhiyanto (Universitas Negeri Semarang, 2020)
Lexical bundles are multi-word expressions that usually hang together. They are considered as a main factor in building fluency in academic discourse; helping to shape meanings and coherence in a text. The objectives of the study are to analyse non-native and native English teachers’ talk in order to explain (1) the use of structural and functional types of lexical bundles in non-native and native English teachers’ talk, (2) the similarities and differences of lexical bundles used in the talk, (3) the relation between structural and functional types of lexical bundles used in the talk. This study is a qualitative study and designed as a classroom discourse analysis. The data are non-native and native English teachers’ talk. The results reveal that non-native and native English teachers used all types of lexical bundles structurally and functionally. Similarly, both teachers performed lexical bundles in form of verb phrase and they mostly functioned as stance expressions. However, they performed them differently in terms of the sub-types. Non-native English teachers used more 1st/2nd person pronoun+VP fragments while native English teachers employed more WH-questions fragments. Functionally, non-native English teachers used lexical bundles more in showing ability while native English teachers performed them more in showing intention/prediction. Both teachers frequently employed lexical bundles with verb phrase structures that functioned as stance expressions. The use of lexical bundles is important for teachers to perform native-like fluency and improve their oral proficiency.